The effect of sward structure and species composition on dietary quality and intake in cattle and sheep grazing the Dohne sourveld. - O'Reagain, Peter John (My University, 1994)
This study investigated the potential effects of species composition and sward structure on dietary quality and intake in cattle and sheep grazing the Dohne Sourveld. In the main experiment, animals were confronted with a range of sward structures at four different sites at different times through the grazing season. Species composition and hence, veld condition, were found to have no dear effect on dietary quality in either cattle or sheep. Conversely, sward structure had a major effect on dietary quality in both animals, with dietary crude protein and in vitro digestibility being strongly related to sward greenness but negatively related. to sward height and herbage mass. Dietary quality was also significantly higher in sheep than in cattle and was markedly higher in the year of the burn than in the subsequent year. (Abbreviation abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: VELD GRASS--SOUTH AFRICA--DOHNE.; RANGELANDS--SOUTH AFRICA--DOHNE.; GRASSLANDS--SOUTH AFRICA--DOHNE.; ARID REGIONS AGRICULTURE--SOUTH AFRICA--DOHNE.; FORAGE PLANTS--SOUTH AFRICA--DOHNE.; GRAZING--SOUTH AFRICA--DOHNE.; CATTLE--FEED UTILIZATION EFFICIENCY--SOUTH AFRICA--DOHNE.; SHEEP--FEED UTILIZATION EFFICIENCY--SOUTH AFRICA--DOHNE.